The role of high serum uric acid levels in androgenic and non-androgenic polycystic ovarian syndrome patients - Ranakishor Pelluri; Kongara Srikanth; Harika Paritala; Vamsi Ravi; Sri Pandu Mukharjee Kamma; Kishan Dravid Piduguralla; Unnam Venkateswarlu; Jalasuthram Subrahmanyam; Kiranmayee Bannaravuri; Thanmayee Thunga; Ragini Vemparala; Sruthi Doddapaneni; et al. (Elsevier, 2021)
Background: Serum uric acid (SUA) has been found to be an independent risk factor for metabolic syndrome (MS). However, the reports pertaining to link between uric acid levels among the androgenic, non-androgenic (clinical) PCOS subjects are conflicting. Hence, it was aimed to determine incidence of hyperuricmia and its association among the PCOS subjects. Methodology: A single centre hospital based cross-sectional study conducted in south India PCOS subjects during the March 2021 to August 2021. A total 80 subjects were recruited and were stratified into androgenic and non-androgenic PCOS with each of forty subjects in both groups. The incidence of hyper uricemica was found to be 66.25% (n = 53). Results: The mean and SD values of metabolic components such as HbA1C and FPG levels and triglycerides, low density lipoproteins and total cholesterol were showing statistically significant (p < 0.05) among the groups. The circulating sex hormone binding globulins (SHBG) are low in both groups. These levels are significantly low in androgenic PCOS subjects. The Total testosterone (TT), SHBG, HOMA-IR and LDL levels were positively correlated with both hyper and non-hyper uricemic groups and remaining parameters showed negative correlation. Conclusion: The incidence of hyperuricemia is high in PCOS subjects. The TT and SHBG, HOMA-IR and LDL levels were positively correlated with both hyper and non-hyper uricemic groups. HbA1C and FPG and FSI are negatively correlated among the groups.